PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Fiqry Fachrezzy Putra (JURNAL RISET AKUNTANSI TIRTAYASA, 2023)
The purpose of this study is to investigate the influence of company characteristics on disclosure called Corporate Social Responsibility (CSR) with institutional ownership as a moderating variable. The sample from the study is a company listed on the LQ45 index of the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The data analysis technique used is multiple regression analysis and moderate regression analysis. The study findings show that company size has a negative effect on CSR disclosure, leverage has a positive effect on CSR disclosure, profitability, and company growth have no effect on CSR disclosure. Institutional ownership can moderate the relationship between firm size and leverage and CSR disclosure, but institutional ownership cannot moderate the relationship between profitability and firm growth on CSR disclosure.